Obesity and acute type A aortic dissection: unraveling surgical outcomes through the lens of the upper hemisternotomy approach - Xia, Lin; Liu, Yu; Yang, Zhonglu; Ge, Yuguang; Wang, Lu; Du, Yejun; Jiang, Hui (Frontiers in Cardiovascular Medicine, 2024)
Background Acute type A aortic dissection (ATAAD) is a pressing cardiovascular emergency necessitating prompt surgical intervention. Obesity, a pervasive health concern, has been identified as a significant risk factor for ATAAD, introducing unique surgical challenges that can influence postoperative outcomes. This study aimed to investigate the outcomes of ATAAD surgery across various body mass index (BMI) categories, focusing on the implications of the upper hemisternotomy (UHS) approach. Methods Between April 2017 and October 2023, 229 patients diagnosed with ATAAD underwent aortic arch intervention via UHS at the General Hospital of Northern Theater Command. Based on BMI (WS/T 428-2013), patients were categorized into normal weight, overweight, and obese. The primary outcomes included perioperative parameters, intraoperative details, and postoperative complications, with specific emphasis on hypoxemia, defined by the Berlin criteria as a PaO2/FiO2 ratio of ≤300 mmHg. Results The average age of the cohort was 50.1 ± 11.2 years with a male predominance (174 males). Preoperatively, 49.0% presented with hypoxemia, with the Obese group exhibiting a significantly elevated rate (77.9%, P < 0.001). Postoperatively, while the Normal group demonstrated a lower thoracic drainage volume 24 h post-surgery [180.0 (140.0) ml; P < 0.001], the Obese group indicated prolonged durations for mechanical ventilation and ICU stay, without statistical significance. Unlike the Normal and Overweight groups, the Obese group showed no notable changes in pre- and postoperative PaO2/FiO2 ratio. No significant difference was observed in severe postoperative complications among the groups. Further ROC curve analysis identifies a BMI cutoff of 25.5 for predicting postoperative hypoxemia, with 76.3% sensitivity and 84.4% specificity. And multivariate analysis reveals BMI and preoperative hypoxemia as independent predictors of postoperative hypoxemia. Conclusion Obesity, although presenting unique challenges in ATAAD interventions, does not necessarily portend adverse outcomes when managed with meticulous surgical planning and postoperative care. The study emphasizes the significance of individualized patient assessment and tailoring surgical strategies, suggesting the potential of UHS in addressing the surgical intricacies posed by obesity in ATAAD patients. Further research is warranted to consolidate these findings.